RISK ANALYSIS OF HYDROPONIC SPINACH PRODUCTION AT SERUA FARM DEPOK CITY - Elpawati Elpawati; Junaidi Junaidi; Wasis Vidya Hajjarwati (AGRIBUSINESS JOURNAL, 2021)
In this study, the causes and impacts of the risks caused will be identified, as well as determining the causes of risks that must be given preventive action first to control the risk of hydroponic spinach production at Serua Farm. The study was conducted by identifying the causes of risk using the Fish Bone diagram by detailing the causes of failure and the consequences of risk based on the source of production risk. The risk analysis uses the House of Risk Phase 1 and 2 methods, as well as the Pareto diagram to map the causative agents of risk that should be given a preventive strategy first.  The risks of hydroponic spinach production faced by Serua Farm are grouped into 23 risk causes and 22 risk events. The results of the risk mapping that occurred in hydroponic spinach production at Serua Farm obtained a total of 12 risk causes that were priorities to be used as risk management and based on the Pareto mapping, 18 preventive risk prevention strategies were obtained to avoid these risks from happening again.